Analisis Malpraktik Pemilu: Intergritas Bawaslu dalam menghadapi kampanye terselubung di acara Reuni Akbar 212 - Fikri Ardiyansyah; Valina Singka Subekti (Journal of Education, Humaniora and Social Sciences (JEHSS), 2021)
This paper aims to examine the hidden campaigns carried out by camp 02 at the 212 grand reunion event, and the actions taken by Bawaslu as election organizer. This study uses analytic qualitative research, namely research that has the aim of analyzing the findings. The results showed that the grand reunion carried out by 212 alumni was a form of covert campaign by camp 02. This was evidenced by the findings explained by the researchers. In addition, the actions taken by Bawaslu were a form of election violations with the DKPP decision regarding the sanctions given to Bawaslu commissioners. In practice, in the field there was a hidden campaign carried out by party 02 at the grand reunion. This is evidenced by the existence of hashtags to replace the president and songs or yells that cornered parties 01. In the third typology it is explained that the election organizer must be neutral and professional. This is different from the findings in the field where a decision was made by one of the commissioners unilaterally without any prior investigation and plenary meeting and only came from television broadcasts. The data were collected through in-depth interviews with sources, and were analyzed qualitatively. This study concluded that the grand reunion carried out by 212 alumni was a form of covert campaign carried out by camp 02. In addition, Bawaslu was proven to have violated ethics by issuing a DKPP decision regarding violations of the code of ethics accepted by DKI Bawaslu and Bawaslu RI by making decisions one-sided so that it is not neutral and professional.